Basic Cardiopulmonary Resuscitation Manual - Morales Gonzalez, Jose A. (IntechOpen, 2013)
The purpose of this publication is to systematize the knowledge necessary to make Cardiopulmonary Resuscitation (CPR) or Cardiorespiratory Resuscitation (CRR) known to nursing health specialists, which translates as a set of temporary and internationally standardized maneuvers assigned to ensure the oxygenation of the vital organs when the blood circulation of an individual stops suddenly, independently of the cause of the Cardiorespiratory arrest (CRA). This knowledge is found correctly delimited in The Basic Cardiopulmonary Resuscitation Manual, which especially emphasizes the step-by-step methodology and techniques to follow for Cardiopulmonary Resuscitation (CPR). This is a basic work that cannot be overlooked by health care specialists, the society, and the public in general, because of the high probability that this situation will present at some moment in life. Thus, it is recommended to be prepared to help some person in an emergency situation. The manual is an excellent consultation work for health professionals. Given that what is expressed in this work is fundamental for life, and its objective is to make known the relevant information concerning the knowledge of CPR.